STUDENTS’ ATTITUDE TOWARD THE USE OF WATTPAD IN READING COMPREHENSION - Rohani Ganie; Khairunnisa Audi Miranda; Muhammad Yusuf (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study attempts to seek what components of reading are affected by reading Wattpad and how the students' attitudes towards the use of Wattpad for reading. This research used a descriptive qualitative method. This research is also supported by the theory of reading attitude proposed by McKenna, et.al. The data for this study were collected from two sources, namely a close-ended questionnaire to 20 English Literature students of Universitas Sumatera Utara and supported by interview with 5 out of 20 selected respondents. The results of this study indicate two main things, namely: (1) Vocabulary is the component of reading that is most affected. As many as 40% of respondents chose vocabulary as the most affected reading component, 35% of respondents chose comprehension ability, 15% of respondents chose reading fluency and 10% of respondents chose phonemic awareness. (2) It was found that 10 respondents were judged to show a positive attitude towards the use of Wattpad, 6 respondents showed a neutral attitude and 4 respondents showed a negative attitude towards the use of Wattpad.